Retention of Uninfected Red Blood Cells Causing Congestive Splenomegaly is the Major Mechanism of Anemia in Malaria - Muhammad Qayyum, Qadeer Ahmed, Muhammad Javaid Iqbal, Muhammad Usman, Salman Ahmad, Salman Khan, Sheheryar Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Malaria has remained rampant in many parts of the world, which is likely to have a direct impacts on the levels of anemia that are brought about by low levels of red blood cells or hemoglobin. Objectives: So, the basic aim of the study is to find the retention of uninfected red blood cells causing congestive splenomegaly is the major mechanism of anemia in malaria. Methodology: This prospective observational study design was conducted at Bolan Medical College Quetta from January 2022 to December 2022. Data were collected from 120 patients suffering from malaria. Clinical assessment is conducted, gathering information on medical history, symptoms, and physical examination findings. Blood samples are obtained from each participant for comprehensive hematological analysis, including CBC, reticulocyte count, and assessment of various red blood cell indices. Results: Mean age of the patients was 35.01±10.2 years. Out of 120, there were 72 male and 48 female patients. There were 25 patients suffering from Splenectomy and most highlighted indication was hemolytic anemia which was 12 (48%), after that splenic trauma 7 (28%) and 6 (24%) were other indications.Mean time since splenectomy was 5±2.5 years.There was a strong positive correlation between splenomegaly and parasite density with correlation coefficient (r) 0.65 and p-value <0.001. Splenomegaly and parasite density emerged as significant predictors of anemia, with splenomegaly showing a stronger negative association (β = -0.45, p < 0.01) compared to parasite density (β = -0.30, p < 0.05). Conclusion: The significant associations observed between splenic filtration stringency, parasite density, and RBC deformability highlight the multifaceted nature of anemia pathogenesis in malaria. Keywords: Malaria, Blood Count, Congestive Splenomegaly, Anemia